Pendidikan Agama Islam sebagai Ekologi Kapital Religius: Integrasi Kapital Manusia, Budaya, Sosial, dan Simbolik dalam Paradigma Tauhid - Dessy Maulana; Hartoni; Januar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study attempts to reconstruct the paradigm of Islamic education through a religious capital ecology approach, which integrates human, cultural, social, and symbolic capital within the framework of the tauhid paradigm. Using the library research method with a philosophical hermeneutics approach, this study analyzes the works of Pierre Bourdieu and a number of Islamic educational thinkers such as Al-Ghazali, Al-Attas, and M. A. Abdullah. The results show that Islamic Religious Education (IRE) acts as an ecosystem that nurtures and maintains various forms of religious capital, which originate from the values of faith, knowledge, charity, and manners. Within this framework, each form of capital does not stand alone but is interconnected within a system of tawhid values that harmonizes the worldly and spiritual dimensions. The concept of Religious Capital Ecology expands Bourdieu's theory of capital by incorporating transcendental and spiritual dimensions, while strengthening efforts to decolonize the epistemology of Islamic education.